Theories of change in Agile Psychology - Rad, Dana; Rad, Gavril (Technium Social Sciences Journal, 2021)
Theory of Change is essentially a detailed illustration and exemplification of how and why a desired change is expected to occur in a certain setting. It is particularly concerned with mapping out or what has been termed as the missing gap between what an intervention or change effort performs and how they contribute to the achievement of desired outcomes. It accomplishes this by first defining the intended long-term objectives and then working backwards from these to determine all of the circumstances (outcomes) that must exist (and how they are causally connected to one another) for the objectives to occur. All of this is stated out in an Outcomes Framework. The Outcomes Framework then serves as the foundation for determining what form of activity or intervention will result in the outcomes listed as prerequisites for reaching the long-term objective. The precise relation between activities and the attainment of long-term goals is better understood using this technique. This results in improved planning since actions are related to a full grasp of how change occurs. It also leads to improved assessment since it allows for the measurement of progress toward the attainment of longer-term goals that extend beyond the identification of program outcomes. For modern managers, working with agile development necessitates the adoption of a new philosophy or psychology. While method is vital to guarantee that the team produces high-quality interventions that fulfills clients’ needs, it's also crucial to remember that the Agile Method emphasizes flexibility, collaboration, and transparency among team members as well as between the team and management. It creates a management climate in which managers exert less control and more facilitation. The manager's responsibility shifts to one of removing bottlenecks, fostering openness and communication, and monitoring the change-driven environment to ensure that the results satisfy goals and criteria but not exerting too much control on the flow of the process of agile development. Change is no longer incorrect; rather, the inability to change is incorrect. Thus, the emphasis of this paper is to raise awareness of the importance of approaching agile psychology with theories of change methodologies.